Sign language in South Africa language planning and policy challenges - Ganiso, Mirriam Nosiphiwo (Rhodes University, Faculty of Humanities, School of Languages, 2011)
This thesis sets out to undertake research into the very important topic of sign language and its usage, particularly in the Western Cape Province of South Africa. Three schools are used in this study. Interviews and questionnaires were used to conduct research with teachers, students and deaf teacher assistants within this context. The analysis of this data is presented in Chapter five of this thesis.
Keywords: Sign language -- Study and teaching -- South Africa; Deaf -- Education -- South Africa; Deaf -- Means of communication